ChemInform Abstract: Supramolecular Explorations: Exhibiting the Extent of Extended Cationic Cyclophanes. Issue 17 (April 2016) - Dale, Edward J.; Vermeulen, Nicolaas A.; Juricek, Michal; Barnes, Jonathan C.; Young, Ryan M.; Wasielewski, Michael R.; Stoddart, J. Fraser
Abstract: Review: 61 refs.